ZmCom1 Is Required for Both Mitotic and Meiotic Recombination in Maize - Wang, Yazhong; Jiang, Luguang; Zhang, Ting; Jing, Juli; He, Yan (Frontiers in Plant Science, 2018)
CtIP/Ctp1/Sae2/Com1, a highly conserved protein from yeast to higher eukaryotes, is required for DNA double-strand break repair through homologous recombination. In this study, we identified and characterized the COM1 homolog in maize. The ZmCom1 gene is abundantly expressed in reproductive tissues at meiosis stages. In ZmCom1-deficient plants, meiotic chromosomes are constantly entangled as a formation of multivalents and accompanied with chromosome fragmentation at anaphase I. In addition, the formation of telomere bouquet, homologous pairing and synapsis were disturbed. The immunostaining assay showed that the localization of ASY1 and DSY2 was normal, while ZYP1 signals were severely disrupted in Zmcom1 meiocytes, indicating that ZmCom1 is critically required for the proper SC assembly. Moreover, RAD51 signals were almost completely absent in Zmcom1 meiocytes, implying that COM1 is required for RAD51 loading. Surprisingly, in contrast to the Atcom1 and Oscom1 mutants, Zmcom1 mutant plants exhibited a number of vegetative phenotypes under normal growth condition, which may be partly attributed to mitotic aberrations including chromosomal fragmentation and anaphase bridges. Taken together, our results suggest that although the roles of COM1 in homologous recombination process seem to be primarily conserved，the COM1 dysfunction can result in the marked dissimilarity in mitotic and meiotic outcomes in maize compared to Arabidopsis and rice. We suggest that this character may be related to the discrete genome context.